2007
DOI: 10.1124/dmd.107.015107
|View full text |Cite
|
Sign up to set email alerts
|

Efflux Transporter Expression and Acetaminophen Metabolite Excretion Are Altered in Rodent Models of Nonalcoholic Fatty Liver Disease

Abstract: ABSTRACT:Efflux transporters are responsible for the excretion of numerous xenobiotics and endobiotics and thus play an essential role in proper liver and kidney function. Nonalcoholic fatty liver diseases (NAFLDs) comprise a spectrum of disorders that range from simple fatty liver (SFL) to nonalcoholic steatohepatitis (NASH). Although the precise events leading to NAFLD are unclear, even less is known about the effects on efflux transporter expression and drug disposition. The purpose of this study was to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
88
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 83 publications
(103 citation statements)
references
References 59 publications
(64 reference statements)
14
88
1
Order By: Relevance
“…Abcc3 and 4 are basolateral efflux transporters that pump various endogenous and exogenous chemicals from hepatocytes to blood; multiple drug and drug metabolites have been identified as substrates for human and mouse ABCC3/Abcc3 and ABCC4/Abcc4 (Kruh and Belinsky, 2003). Induction of Abcc3 and Abcc4 by chemical inducers or nonalcoholic steatohepatitis is associated with altered vectorial excretion of acetaminophen glucuronide (Lickteig et al, 2007a). In contrast with Abcc3 and 4, Abcc1 mRNA expression was decreased in livers of DIO mice.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Abcc3 and 4 are basolateral efflux transporters that pump various endogenous and exogenous chemicals from hepatocytes to blood; multiple drug and drug metabolites have been identified as substrates for human and mouse ABCC3/Abcc3 and ABCC4/Abcc4 (Kruh and Belinsky, 2003). Induction of Abcc3 and Abcc4 by chemical inducers or nonalcoholic steatohepatitis is associated with altered vectorial excretion of acetaminophen glucuronide (Lickteig et al, 2007a). In contrast with Abcc3 and 4, Abcc1 mRNA expression was decreased in livers of DIO mice.…”
Section: Discussionmentioning
confidence: 98%
“…Given the increased number of persons presenting with NAFLD and NASH and emerging evidence that fatty liver affects transporter expression in humans and rodents (Lickteig et al, 2007a), there is a growing need to better predict drug absorption, distribution, metabolism, and elimination, efficacy, and drug-induced liver injury using rodent models of obesity and diabetes.…”
Section: More and Slittmentioning
confidence: 99%
“…For example, the expressions of the bile salt export pump, MRP2, and OATP(s) were all reported to be decreased after 24 h of reperfusion in rats, while multidrug resistance protein 1B was increased. [22][23][24] In nonalcoholic fatty liver disease, expression of MRP2 has been reported to be upregulated, 41 whereas it was relatively well preserved in cholestasis and primary biliary cirrhosis. 42,43 Interestingly, mRNA and protein levels of the OATP2 transporter appeared contradictory after 4 h of reperfusion [ Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy and toxicity of drugs targeting the central nervous system are largely deter-mined by the function and expression of these transporters and by their selectivity and affinity toward the substrates [6,7] . Several studies have verified that the functions of P-gp and Mrp2 at BBB are affected by various disease states, including diabetes mellitus [8,9] , acute myeloid leukemia [10] , cancer [11] and liver failure [12][13][14] . Our previous studies have also demonstrated that both the function and expression of P-gp and Mrp2 are markedly altered in brain tissues in thioacetamide/ hyperammonemia-induced liver dysfunction rodent models [15,16] .…”
Section: Introductionmentioning
confidence: 99%